CIAT's Plant Phenomics Platform: Movable rainout shelter - International Center for Tropical Agriculture (2016)
CIAT has four movable rainout shelter equipped with automated irrigation systems, which are being used to promote the development and adoption of low-input rice production systems in Latin America, through genetic improvement and advanced crop management technologies. These are also used to conduct drought tolerance studies in bean plants.